Lights should support circadian rhythms: evidence-based scientific consensus - Moore-Ede, Martin; Blask, David E.; Cain, Sean W.; Heitmann, Anneke; Nelson, Randy J. (Frontiers in Photonics, 2023)
For over a hundred years, the lighting industry has primarily been driven by illumination aesthetics, energy efficiency and product cost with little consideration of the effects of light on health. The recent widespread replacement of traditional light sources by blue-enriched LED lights has heightened concerns about the disruption of the blue-sensitive human circadian system by these LED lights and their impact on the multiple health disorders linked to circadian disruption. Despite these health concerns, less than 0.5% of the lighting sold today modifies spectral content and intensity between day and night. We report that 248 scientists, with a total of 2,697 peer-reviewed publications on light and circadian clocks since 2008, reached consensus on 24 25 statements about the impact of light on circadian rhythms and health based on accumulated scientific evidence, including support for the widespread introduction of circadian lighting and warning labels on blue-enriched LED lights indicating they "maybe harmful if used at night".